Philosophical Approach in Islamic Education: Improving the Quality of Education Through Dialogue and Reflection - Dani Rustani; Hermina Nurhasanah; Serly Nurmayanti; Yayan Hidayat (Inovan Publisher, 2024)
In this scientific paper, the author lists several problems that are currently occurring in the world of education in Indonesia, one of which is the learning process which is currently experiencing a lot of development and progress. With this development and progress, it is inseparable from the urgent demands to improve the quality of education, how to improve the quality of education today? The main purpose of writing this scientific paper is to find out the strategies carried out by educators towards students to improve the quality of education in Indonesia. This study utilizes a Qualitative Descriptive approach, which begins with finding primary information focused on literature studies (Library Research), namely a study that focuses on finding library data and describing it, a systematic description of data collections, descriptive descriptions do not use numbers. The results of this study state that the philosophical approach between educators and students by applying the dialogue and reflection learning method will greatly influence the improvement of the quality of education in Indonesia.